Spark and Sparkle – „Iskra i gra”. O tłumaczeniu poezji absurdalnej na przykładzie wiersza Ogdena Nasha - Skrzypecki, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is a short presentation of a translation concept created by an American cognitivist and physicist Douglas Hofstadter included in his book Le Ton beau de Marot. The principles of the concept are presented by means of a metaphor. Translation is a game of, only partially conscious, participation in an infinite loop: words evoke images and images – words. The contact with the original text creates images in the translator’s mind that he or she translates by means of language structures into sentences/verses of the target language. This cognitive intuition is paired with a structural category of Stanisław Barańczak’s semantic dominant. This methodological, structural-cognitive pair is a starting point for the analysis of Barańczak’s translation of Ogden Nash’s The Dog. The stylistic and formal solutions (especially rhymes) used by the translator are analysed, but the main goal of the text is to capture the elusive, i.e. the analysis of the interlinguistic and ‘inter-mental’ translation of the absurd sense of humour.